Annotated Checklist and Conservation Status of Mammal Species in Sarpang District, Bhutan - Jigme Tenzin; Phub Dhendup; Dago Dorji; Sangay Nidup; Phuntsho Thinley (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
Bhutan has a total geographical area of 38,394 Km² located in between the Indo-Malayan and Palearctic region, out of which 51.44% (19750.75 km²) of its total geographical area has been designated as the protected area.  However, none of the districts have a structured baseline checklist of mammal species documented till date. Therefore, Sarpang Forest Division under the Department of Forests and Park Services had carried out five rigorous camera trap surveys including a nationwide tiger survey that covers representable areas of the district from 2014 till 2020. The survey shows that district has 36 mammal species that belong to 18 families under seven orders. Felidae and Cervidae families has the highest species abundance (n = 17%), while, Canidae, Herpestidae, Leporidae, Manidae, Melinae, Muridae, Mustelidae, Tupaiidae, Proboscidae, Pteromyidae, Suidae and Ursidae were the lowest (n = 3%). Above all, Sarpang homed 29.90% of total mammal species of Bhutan, out of which 3% of mammal species were categorized under Critically Endangered, 14% Endangered, 14% Vulnerable, 22% Near Threatened, and 47% Least Concern as per IUCN Red List. However, only 20 mammal species are listed under CITES and nine in Schedule I of Forest and Nature Conservation Act of Bhutan, 1995. Therefore, landscape-based planning such as the Division-based Conservation & Management plan; periodic monitoring of wildlife species using camera traps, and validation of Schedule I species are suggested for long-term conservation and management of globally threatened species inside the landscape of Sarpang district in Bhutan.